Beating the bullshitters. - Zuckerman, Ethan (Prospect, 2023)
Once such systems can consistently generate running computer code, we may see the rise of so-called "no code" tools, where an AI writes functional computer code from a simple text prompt, radically changing how software is created. In late 2022, machine learning start-up OpenAI released a tool called ChatGPT. ChatGPT is sufficiently good at copying writing styles that academic essays come complete with footnotes.